DEM-FDM coupled simulation of the interlock behavior between adjacent geogrids using pullout test - Cheng Chen; Jiang-Cheng Zhong; Glenn McDowell; Xiao-Dong Lin; Rui Rui; Lei Zhang (Geotextiles and Geomembranes, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Model tests on the evolution characteristics and aggravation effects of seepage erosion in shield tunnels under train vibration - Hui-Hao Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Xue-Liang Zhang; Si-Rui Chen; Jie Yang (Tunnelling and Underground Space Technology, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

Vibration-exacerbated suffusion in soils with different gradations: a coupled DEM–PNM study - Si-Rui Chen; Dong-Mei Zhang; Xue-Liang Zhang; Hui-Hao Chen; Zhao-Geng Chen; Xiao-Chuang Xie (Computers and Geotechnics, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Origins of Miocene basaltic magmatism in the western Yarlung-Tsangpo Suture Zone, southern Tibet: Insight into the lateral and longitudinal tearing of the subducted Indian continental slab - Jianbo Cheng; Xianshu Dong; Yalin Li; Shuai Li; Siqi Xiao; Wenjun Bi; Rui Zhou (Chemical Geology, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Encoding intrinsic rare-earth dissolution selectivity into deep eutectic solvents via coordination-active functional group design - Zhihan Zhang; Guobiao Li; Zhi Wang; Wanhai Xiao; Yong Lin; Shuping Cheng; Rui Min; Jian Wu; Mingqing Liu; Dong Wang (Journal of Cleaner Production, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Self-enhancing climatic resilience of surface soil through bio-carbonation constructed barrier - Rui Wang; Chao-Sheng Tang; Guang-Hui Lei; Xiao-Hua Pan; Zhi-Hao Dong; Shao-Dan Wang; Xiancai Lu (Engineering Geology, 2026)

Biomass ratio regulates methane conversion and carbon fixation in a methanotrophs-microalgae symbiotic system: Efficiency optimization and mechanisms driven by co-metabolism - Xiaoqian Li; Xiao Lin; Ziyi Dong; Rui Zhou; Qigui Niu (Water Research, 2026)

Suffusion in shield tunnel surrounding soils under train vibration using an improved DEM-PNM coupling method - Si-Rui Chen; Dong-Mei Zhang; Xiao-Chuang Xie; Zhao-Geng Chen; Hui-Hao Chen; Hai-Yun Li (Tunnelling and Underground Space Technology, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Montmorillonite-enhanced nitrogen fixation and emission reduction during food wast pyrolysis - Hongyuan Chen; Danni Li; Yazhuo Wang; Yaoxin Xiao; Dong Liang; Gangqi Cheng; Rui Shan; Haorang Yuan; Yong Chen (Fuel, 2026)

Evolution of soil arching under different initial water-saturation conditions via coupled SPH-DEM method - Rui-Xiao Zhang; Dong Su; Xiang-Sheng Chen; Xiu-Song Shi; De-Jin Zhang (Computers and Geotechnics, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Long-term removal of root carbon inputs has a great negative impact on grassland soil bacterial diversity, network stability and carbon and nitrogen cycling function - Rongrong Wu; Jilin Zhang; Haiyan Zhang; Xiao Zhang; Biao Dong; Yu Shi; Xin Jing; Rui Xiao; Cancan Zhao (Applied Soil Ecology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Generation of xanthohumol derivatives through fungi-mediated biotransformation - Yina Xiao; Yutong Cheng; Shi Shi; Rui Li; Huijun Dong; Fubo Han (Natural Product Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Identification and evaluation of odor emissions from a petrochemical production area in China - Yunxia Feng; Jinchan Peng; Yirong Guo; Qingrun Li; Anshan Xiao; Rui Dong; Dewu Ding; Mingjun Li (Atmospheric Pollution Research, 2026)

Environmental relevant concentrations of TBBPA cause complex toxicological mechanisms - Yuxing Liao; Yilin Wang; Hao Dong; YaJie Lin; Yuxi Xiao; Rummana Jaman; Mohith Mohan; Farheen Azim; Rui Lu; Tengji Zhao; Jiao Zhu; Guiyuan Chen; et al. (Toxicology Letters, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Green catalytic degradation of antibiotics via endogenous magnetite in bottom slag from agroforestry biomass direct-fired power plants - Junnan Rui; Jinxi Wang; Xiaoyu Xiao; Genhe He; Chunxiao Chen; Zengsheng Zhang; Zhiqiang Dong; Yuping Qiu (Journal of Environmental Chemical Engineering, 2025)

Functional insights into JrWOX5: a WOX transcription factor regulating adventitious rooting and plant architecture in walnut - Rui-xue Gao; Pu Zhang; Ying-ying Chang; Li Song; Xiao-bo Song; Dong Pei (Plant Cell Reports, 2025)

Real-time rockburst warning using microseismic multi-feature parameters based on the PSO-GRNN model - Wen Xuan Dong; Qing He Zhang; Xiao Rui Wang; He Peng Dong; Chuan Bing Wang; Sheng tao Wang (Natural Hazards, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

Miocene N-MORB- and OIB-type diabase dikes in the western Yarlung Tsangpo suture zone, southern Tibet: Insights into the Indian slab tearing and asthenosphere–lithosphere interaction - Jianbo Cheng; Yalin Li; Xianshu Dong; Siqi Xiao; Shuai Li; Wenjun Bi; Rui Zhou (Lithos, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

Theoretical calculation model of the soil arching effect considering tunnel influence - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Xiang-Sheng Chen (Tunnelling and Underground Space Technology, 2025)

Tech-policy integrated validation of spatiotemporal energy-emissions efficiency in public bus systems - Yaxi Xiao; Yangbin Dong; Rui Xue; Zhaocai Meng; Bai Li; Yonghui Hu; Zhanyong Wang (Transportation Research Part D: Transport and Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Enhancing flame retardancy and mechanical properties of epoxy/carbon fiber composites via a metal-phosphorus synergistic interface structure - Dou Hu; Guo-rui Zhang; Xiao-dong Qi; Jing-hui Yang; De-xiang Sun; Yong Wang (Chemical Engineering Journal, 2025)

Modification of red mud using K/Ca doping to enhance its oxygen-donating performance in chemical looping gasification of biomass waste - Rumeng Zhang; Xiao Li; Rui Dong; Xianliang Meng; Bo Zhang; Shi Yu (Biomass and Bioenergy, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Influence of biomass ashes on the structural evolution and oxygen-donating capacity of red mud during chemical looping gasification - Xiao Li; Rumeng Zhang; Rui Dong; Xianliang Meng; Pei Li; Chao Ni; Bo Zhang (Waste Management, 2025)

Thiocyanate degradation by mixed bacterial consortia: Adaptive mechanism in response to thiocyanate stress and metabolic pathway - Xuejiao An; Rui Zhao; Liuwei Wang; Xiaoshuang Xiao; Zihang Xu; Shulin Zhang; Dong Xie; Yao Xiao; Qinghua Zhang (Environmental Research, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Highly selective and reversible adsorption of trace gaseous ammonia by a stable nanoporous carboxylic acid-functionalized silica aerogel - Zai-Dong Shao; Ting-Ting Hu; J. Paul Chen; Qi-Jun Zhang; Peng Wu; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Chemical Engineering Journal, 2025)

Synergistic adsorption-catalysis system based on the advanced oxidation technology of single-atom MOFs: Selective degradation and contribution to different ionization potential pollutants - Si-Han Zhou; Rui-Dong Wang; Yun Yang; AiJin Xiao; Xuejun Pan; Feng-zhi Jiang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Global rehabilitation research equality index across health conditions during 1990–2019: an alignment analysis between bibliographic and epidemiological data - Xin Guo; Jiakang Huo; Wanwei Dai; Tong Wang; Han Xiao; Wenjing Zhao; Xuanyu Shi; Xueheng Wang; Yang Gao; Zhi Li; Rui Zhan; Wenli Xu; et al. (Science Bulletin, 2025)

Promotional role of Ru in bimetallic catalysts for selective transfer hydrogenation of bio-based furfural - Yaoxin Xiao; Yazhuo Wang; Jun Zhang; Gangqi Cheng; Dong Liang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Performance improvement and the mechanisms of red mud oxygen carrier in chemical looping gasification using strontium doping strategy - Xiao Li; Rui Dong; Rumeng Zhang; Yi Zhang; Pengfei Lu; Xianliang Meng; Pei Li (Chemical Engineering Journal, 2025)

A review of emission characteristics and risk assessments of volatile organic compounds in petrochemical industry areas - Jinchan Peng; Yunxia Feng; Anshan Xiao; Bo Li; Dewu Ding; Guolong Wang; Rui Dong (Environmental Pollution, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

A unified particle method for fluid simulation in ship fire scenario - Rui Tao; Xianku Zhang; Hongxiang Ren; Yaxin Dong; Xiao Yang (Ocean Engineering, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Room temperature shape self-adjustable tough hydrogel based on multi-physical crosslinking - Jun-Bo Hou; Zhi-Chao Jiang; Yao-Yu Xiao; Rui-Dong Cheng; Yue Zhao (Chemical Engineering Journal, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Effect of surcharge width on evolution of soil arching for active and passive trapdoor - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin (European Journal of Environmental and Civil Engineering, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Effective decapsulation method for photovoltaic modules: Limonene-induced EVA controlled swelling under sonication and debonding mechanism analysis - Rui Min; Weikai Deng; Zhi Wang; Tao Qi; Zhihan Zhang; Wanhai Xiao; Guoyu Qian; Dong Wang (Journal of Cleaner Production, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

Nitrate leaching characteristics of red soils from different parent materials in subtropical China - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Gan-Lin Zhang (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Tree-ring structured phase change materials with high through-plane thermal conductivity and flexibility for advanced thermal management - Wan-jun Jiang; Rui-qing Wang; Ting-yu Zhu; Mai Feng; De-xiang Sun; Jing-hui Yang; Xiao-dong Qi; Yong Wang (Chemical Engineering Journal, 2024)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Soil arching in ground with tunnel: Effect of distance between tunnel and trapdoor - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Hao Xiong; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Volatile organic compounds during routine production and planned shutdown of a petrochemical refinery: Emission characteristics, source and risk assessment - Yunxia Feng; Guolong Wang; Rui Dong; Bo Li; Dewu Ding; Jinchan Peng; Anshan Xiao (Atmospheric Pollution Research, 2023)

Gut Microbiota in Ischemic Stroke: Role of Gut Bacteria-Derived Metabolites - Wei Zhang; Xiao Yu Dong; Rui Huang (Translational Stroke Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Investigation of the soil arching evolution in the ground with or without a tunnel - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Tai-Feng Zhu; Guoping Lei; Xiang-Sheng Chen (Transportation Geotechnics, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Guide isolation of guaiane-type sesquiterpenoids from Daphne tangutica maxim. And their anti-inflammatory activities - Rui Guo; Zhi-Kang Duan; Qian Li; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Trophic Niche Partitioning of Five Sciaenidae Species Sampled in Zhoushan Archipelago Waters via Stable Isotope Analysis - Jing Wang; Ri-Jin Jiang; Yi Xiao; Rui Yin; Feng Chen; Yong-dong Zhou; Han-Xiang Xu (Frontiers in Marine Science, 2022)
Sciaenid fishes are usually associated with large freshwater inputs and are the most important economic fish on the coastal shelf off mainland China. To compare the differences in ecological niche and resource sharing among different populations of Sciaenidae species, we collected samples of Larimichthys polyactis , Collichthys lucidus , Johnius belangerii , Nibea albiflora , and Miichthys miiuy from Zhoushan Archipelago waters from 2019 to 2021 and investigated the carbon and nitrogen isotopic values in muscle tissues, the contribution of each food resource, and trophic niche widths and overlaps. Significant differences were observed in both isotopes in the muscles of the five Sciaenid species. Zooplankton was a key food resource for all Sciaenid species. In addition to zooplankton, J. belangerii , N. albiflora , and M. miiuy also fed on benthos organisms. C. lucidus presented a wide trophic niche width and had extensive habitat use. The trophic niche occupied by N. albiflora and M. miiuy was narrow; they presented a high trophic level, with a high degree of trophic niche overlap. This study showed that sciaenid fishes have overlapping trophic niches due to their common feeding on zooplankton, and differences in body size, migration, habitat, and feeding choices led to the reasonable sharing of resources among the five sciaenid fishes, allowing the coexistence of these species.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Nitrate runoff loss and source apportionment in a typical subtropical agricultural watershed - Yue Dong; Jin-Ling Yang; Xiao-Rui Zhao; Shun-Hua Yang; Jan Mulder; Peter Dörsch; Gan-Lin Zhang (Environmental Science and Pollution Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Selective regulation in ribosome biogenesis and protein production for efficient viral translation - Hui-Jun Dong; Rui Zhang; Yu Kuang; Xiao-Jia Wang (Archives of Microbiology, 2021)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Similar simulation device for unloading effect of deep roadway excavation and its application - Chun-liang Dong; Guang-ming Zhao; Xiao-yu Lu; Xiang-rui Meng; Ying-ming Li; Xiang Cheng (Journal of Mountain Science, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Variable-grid reverse-time migration of different seismic survey data - Xiao-Dong Sun; Zhen-Chun Li; Yan-Rui Jia (Applied Geophysics, 2017)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

MiR-28 inhibits cardiomyocyte survival through suppressing PDK1/Akt/mTOR signaling - Rui-Yao Zhu; Di Zhang; Han-Dong Zou; Xiao-Shu Zuo; Qing-Shan Zhou; He Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke - Xiao-Lin Gu; Lin Liu; Xiang-Dong Lu; Zhen-Rui Liu (Molecular Neurobiology, 2016)

Azimuthal cement evaluation with an acoustic phased-arc array transmitter: numerical simulations and field tests - Xiao-Hua Che; Wen-Xiao Qiao; Xiao-Dong Ju; Rui-Jia Wang (Applied Geophysics, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Ectopic expression of UGT75D1, a glycosyltransferase preferring indole-3-butyric acid, modulates cotyledon development and stress tolerance in seed germination of Arabidopsis thaliana - Gui-Zhi Zhang; Shang-Hui Jin; Xiao-Yi Jiang; Rui-Rui Dong; Pan Li; Yan-Jie Li; Bing-Kai Hou (Plant Molecular Biology, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Evaluation of yeasts from Tibetan fermented products as agents for biocontrol of blue mold of Nashi pear fruits - Hao Hu; Yang Xu; Huang-ping Lu; Rui Xiao; Xiao-dong Zheng; Ting Yu (Journal of Zhejiang University-SCIENCE B, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Phytoremediation potential of Pteris vittata L. under the combined contamination of As and Pb: beneficial interaction between As and Pb - Xiao-ming Wan; Mei Lei; Tong-bin Chen; Guang-dong Zhou; Jun Yang; Xiao-yong Zhou; Xi Zhang; Rui-xiang Xu (Environmental Science and Pollution Research, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Estimate of eddy energy generation/dissipation rate in the world ocean from altimetry data - Chi Xu; Xiao-Dong Shang; Rui Xin Huang (Ocean Dynamics, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

14-3-3γ and Neuroglobin are New Intrinsic Protective Factors for Cerebral Ischemia - Yan Dong; Rui Zhao; Xiao Qian Chen; Albert Cheung Hoi Yu (Molecular Neurobiology, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)